Good practice intervention for clinical assessment and diagnosis of atopic dermatitis: Findings from the atopic dermatitis quality of care initiative. Issue 3 (30th December 2021) - Weidinger, Stephan; Nosbaum, Audrey; Simpson, Eric; Guttman, Emma
Abstract: Atopic dermatitis (AD) is frequently misdiagnosed and undertreated, resulting in increased morbidity. In 2019, the Atopic Dermatitis Quality of Care Initiative was launched globally to investigate barriers to AD care and note good practice interventions to improve care. The initiative included a literature review to define the challenges in AD and a survey of 32 AD centers to define good practice interventions. One topic studied was best practices for clinical assessment and diagnosis. The literature review revealed the primary gaps included difficulty differentiating AD from other skin disorders, diagnosing atypical AD, staging AD severity in individual patients, and delays in assessment and treatment due to referral time lag. The best clinical practices used by leading AD centers included the use of validated diagnostic criteria, established AD scoring tools including patient‐reported outcome measures and electronic health records (EHR), the formation of multidisciplinary teams (MDTs), and improved communication between health care providers (HCPs) and patients. Most centers worked with patient advocacy groups and implemented educational programs for HCPs. AD centers are overcoming issues in AD care. Educating health care providers and the public, using screening surveys, using established guidelines, and communicating with MCTs and patients through EHRs are the most frequently used strategies.